2015
DOI: 10.1038/srep08367
|View full text |Cite
|
Sign up to set email alerts
|

IER3 is a crucial mediator of TAp73β-induced apoptosis in cervical cancer and confers etoposide sensitivity

Abstract: Infection with high-risk human papillomaviruses (HPVs) causes cervical cancer. E6 oncoprotein, an HPV gene product, inactivates the major gatekeeper p53. In contrast, its isoform, TAp73β, has become increasingly important, as it is resistant to E6. However, the intracellular signaling mechanisms that account for TAp73β tumor suppressor activity in cervix are poorly understood. Here, we identified that IER3 is a novel target gene of TAp73β. In particular, TAp73β exclusively transactivated IER3 in cervical cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 55 publications
(68 reference statements)
1
26
0
Order By: Relevance
“…This pattern is highly reminiscent of the product of the immediate early gene X1 (IEX-1/IER3), which was previously reported to sequester MCL-1 in response to DNA damage [ 25 ], at least partially co-localizing with PML bodies in HeLa cervical carcinoma cells [ 26 ]. In this cell line, upregulation of IER3 was required for DNA damage to induce apoptosis [ 27 ]. Intriguingly, we found IER3 to be strongly induced upon conditional EWS-FLI1 knockdown in A673/TR/shEF (Figure 4E ) and, with the only exception of SK-N-MC, in four of five additional cell lines upon transient knockdown of EWS-FLI1 [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…This pattern is highly reminiscent of the product of the immediate early gene X1 (IEX-1/IER3), which was previously reported to sequester MCL-1 in response to DNA damage [ 25 ], at least partially co-localizing with PML bodies in HeLa cervical carcinoma cells [ 26 ]. In this cell line, upregulation of IER3 was required for DNA damage to induce apoptosis [ 27 ]. Intriguingly, we found IER3 to be strongly induced upon conditional EWS-FLI1 knockdown in A673/TR/shEF (Figure 4E ) and, with the only exception of SK-N-MC, in four of five additional cell lines upon transient knockdown of EWS-FLI1 [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cyclin-dependent kinase 3 (CDK3), targeted by Novel_237, was reported that the downregulation of activities of CDK3-related kinase could promote cell apoptosis in the rat (Braun et al, 1998). Immediate early response 3 (IER3), targeted by Novel_327, was also involved in enhancing (Zhou et al, 2017) or mediating (Jin et al, 2015) cell apoptosis. Polycystic kidney and hepatic disease gene 1 (PKHD1), targeted by Novel_401, has been discovered to induce cell apoptosis, after being downregulated through the PI3K and NF-kB pathways (Sun et al, 2011).…”
Section: Functional Analysis Of Degs In Pl Vs MLmentioning
confidence: 99%
“…6-Phosphofructo-2-kinase/fructose-2,6-biphosphatase 4 (PFKFB4), is a key kinase in Warburg pathway [ 34 ], has been found to be associated with a variety of cancers, including breast cancer [ 35 ], prostate cancer [ 36 ] and glioblastoma [ 37 ], promoting the progression and metastasis of cancer, and may become an effective molecular target of anti-tumor drugs. It was found that the expression of immediate early response gene 3 (IER3) was increased in advanced cancer [ 38 , 39 ], but some studies have found that IER3 can also promote tumour cell apoptosis and has anti-tumour activity, such as lower expression in CC tissues [ 40 ], and increasing the expression of IER3 can enhance the sensitivity of CC cells to radiotherapy [ 41 ]. In contrast, in our study, we found that IER3 exists as a risk factor.…”
Section: Discussionmentioning
confidence: 99%